Efektivitas Pelaksanaan Perubahan Batas Usia Nikah Menurut Undang-Undang Nomor 16 Tahun 2019 Tentang Perkawinan Pada Masyarakat di Kabupaten Sarmi - Pelupessy, Eddy; Solossa, Marthinus; Ketaren, Dahliana; Firman, Firman; Mudi, Vivilia Agnata (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Effectiveness of Implementation of Changes to Marriage Age Limit According to Law Number 16 of 2019 concerning Marriage in the Community in Sarmi Regency, and Factors Influencing the Effectiveness of Implementation of Changes to Marriage Age Limit Based on Law Number 16 of 2019 in Sarmi Regency. The factors that cause the ineffectiveness of the implementation of changes to the marriage age limit as regulated by Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage in the community in Sarmi Regency are influenced by several factors, including: 1. Legal Factors, namely the enactment of several provisions that do not stipulate adult age limits such as Customary Law and Islamic Law (KHI); 2. Law enforcement factors, for example, KUA officers who are less active in disseminating information about the enactment of the Law regulating changes to the marriage age limit to the community; 3. Community factors, namely parties who have an interest in the implementation of marriage due to certain reasons or conditions so that marriage must be carried out; 4. Cultural or Customary Factors, related to legal culture, namely the legal awareness of the community in choosing to submit to applicable national laws or customary laws or religious provisions that they adhere to; 5. Facilities and Infrastructure, one of which is the existence of Religious Courts and KUA which are far from where people live in remote villages.